Combining Phosphate and Bacteria Removal on Chemically Active Filter Membranes Allows Prolonged Storage of Drinking Water. (5th August 2013) - Rotzetter, A. C. C.; Kellenberger, C. R.; Schumacher, C. M.; Mora, C.; Grass, R. N.; Loepfe, M.; Luechinger, N. A.; Stark, W. J.
<x xml:space="preserve">Abstract</x> A chemically active filtration membrane with incorporated lanthanum oxide nanoparticles enables the removal of bacteria and phosphate at the same time and thus provides a simple device for preparation of drinking water and subsequent safe storage without using any kind of disinfectants. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>